Evaluation of silver nanoparticles Biosynthesized by Entomopathogenic fungus Entomophthora muscae against larval instars of housefly Musca domestica - R. Mahmood, Hussein (Al-Qadisiyah Journal of Pure Science, 2018)
The research aimed to test the toxicity of silvernanoparticles produced by E.muscae The results explainened that this fungus has ability to synthesize silver nanoparticles and this was confirmed by color change of cell filterate in reaction solution ,the color changed from colorless to yellowish and by UV-Visible spectrophotometer at 420Nm.Bioassay tests pointed out that silver nanoparticles have high toxicity against laraval stages of Musca domestica .The proportion of mortility was the highest against firtst star (95-100%) in all tested concentrations.The lowest mortility was 60,75,83,95and100%at 2,4,6,8,10mg/L subsequently against the third star after 24hours ,while The mortilities of the third star amounted to 70,78,89,97,100% in all the above mentioned concentrations respecively and in the same period.It is suggestive that this rapid synthesis of silver nanoparticles can be used for developing a biological process for housefly .